Preface for the CCAMT 2004 (India) and the 3rd ICAMT 2004 (Malaysia) conferences - VENKATESH, V (ELSEVIER SCIENCE SA, 2007)
Preface for the CCAMT 2004 (India) and the 3rd ICAMT 2004 (Malaysia) conferences